Voting over tax schedules in the presence of tax avoidance - Jesper Roine (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
This paper reconsiders the classical problem of majority voting over tax schedules, adding the possibility to avoid taxes. In this setting preferences over tax schedules are not determined by earned income, but rather by taxable income, which depends on the joint decisions of labor supply and tax avoidance investments. The ordering of earned- and taxable income are shown to be the same if the tax avoidance function is log concave.
Keywords: C62; D70; H20; 330; Tax avoidance; Majority voting; Order-restricted preferences; Single-crossing condition; Steuervermeidung; Wahlverhalten; Einkommensumverteilung; Theorie